Locally controlling dynamic exchange reactions in 3D printed thiol-acrylate vitrimers using dual-wavelength digital light processing. Issue 21 (12th May 2021) - Rossegger, Elisabeth; Moazzen, Khadijeh; Fleisch, Mathias; Schlögl, Sandra
Abstract : A photolatent transesterification catalyst is applied to locally switch on and control topological rearrangements in 3D printable thiol-acrylate vitrimers. Abstract : Vitrimers are covalent adaptable polymer networks, which are able to rearrange their topology in response to an external stimulus. Below the topological freezing temperature ( T v ) they behave like a classic thermoset, whilst above T v, they become malleable, weldable and recyclable. However, vitrimers mainly rely on thermo-activated dynamic exchange reactions, which suffer from a lack in spatial control. Herein, we introduce triphenylsulfonium phosphate as a latent transesterification catalyst, which releases strong Brønsted acids upon UV exposure (365 nm). Once locally formed, the acids are able to efficiently catalyse thermo-activated transesterifications as confirmed by stress relaxation studies. The latent catalyst is introduced into visible light (405 nm) curable thiol-acrylate resins, whose fast curing kinetics enable the additive manufacturing of precise 3D objects. Due to the orthogonality between the curing reaction and the photo-activation of the catalyst, transesterifications can be selectively switched on in the photo-cured vitrimer simply by UV-light exposure. By using a dual-wavelength digital light processing 3D printer, operating at 405 and 365 nm, the catalyst is locally activated during the layer-by-layer build-up of the 3D structures. This enables the fabrication of soft active devices, which undergo locally controlled topology arrangements above the networks' T v .